A Human Trafficking Educational Program and Point-of-Care Reference Tool for Pediatric Residents - Anjali Garg; Preeti Panda; Sindhoosha Malay; Jerri A. Rose (Association of American Medical Colleges, 2021)
Introduction Trafficked youth experience complex health issues such as substance abuse, severe physical trauma, and sexual health problems, with many entering trafficking between 15 and 17 years old. There is increasing awareness of the need to educate pediatric health care providers on identifying and aiding trafficked children; however, critical gaps in the literature exist regarding educational sessions specific to the human trafficking of pediatric patients. Our objective was to implement and evaluate a survivor-informed educational session for pediatric resident physicians to improve identification of and assistance to trafficked youth in the clinical setting. Methods We designed an educational session on human trafficking, which included a 60-minute interactive didactic presentation and distribution of a point-of-care reference tool, in collaboration with a survivor of human trafficking, for 59 pediatric trainees in 2019. We utilized pre/post knowledge assessments. Data analysis included descriptive statistics and Fisher exact analysis. Results Of 99 total eligible residents, 59 (59%) participated. Statistically significant increases in correct identification of hypothetical trafficked youth and next steps for intervention were observed. Over 80% of participants reported comfort with defining, recognizing, referring to, and understanding health consequences of human trafficking on the postassessment, compared to 25% on the preassessment (p < .001). Discussion Our educational session resulted in statistically significant increased comfort in identification of human trafficking victims and can be replicated at other institutions. The point-of-care reference tool-which can be adapted for use in different settings-can guide pediatric residents in managing suspected trafficked youth in the clinical setting.